1981
DOI: 10.1136/bjo.65.8.536
|View full text |Cite
|
Sign up to set email alerts
|

A noninvasive tonometer in the measurement of the effects of pindolol and timolol on intraocular pressure in normal subjects.

Abstract: tests so that those in whom 5 consecutive measurements showed a difference of more than 3 mmHg were excluded. Measurements in 62 of 94 eyes showed a variation of 3 mmHg or less, and these were considered suitable for the definitive studies. All preparations were administered by a third party to ensure double-blindedness on the part of subject and investigator, and were instilled into the left eye. Intraocular pressure' 3 and radial pulse rate over 1 minute after 5 minutes at rest (sitting) were measured before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In patients with elevated IOP, concentrations of 0.1%, 0.25%, 0.5%, 1.0%, and 1.5% provided statistically significant IOP reductions compared with baseline and/or controls (untreated or placebo-treated eyes). 34 , 38 , 43 , 46 , 47 Even a concentration as low as 0.008% (administered as gel or solution) was effective in lowering IOP in patients with OHT and a baseline IOP >22 mmHg, compared with placebo controls. 39 In contrast, studies of healthy volunteers with baseline IOP of approximately 13–14 mmHg reported no significant IOP-lowering effect when treated with timolol 0.008% or 0.025%, 42 or 0.0625%, 0.125%, or 0.25%.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In patients with elevated IOP, concentrations of 0.1%, 0.25%, 0.5%, 1.0%, and 1.5% provided statistically significant IOP reductions compared with baseline and/or controls (untreated or placebo-treated eyes). 34 , 38 , 43 , 46 , 47 Even a concentration as low as 0.008% (administered as gel or solution) was effective in lowering IOP in patients with OHT and a baseline IOP >22 mmHg, compared with placebo controls. 39 In contrast, studies of healthy volunteers with baseline IOP of approximately 13–14 mmHg reported no significant IOP-lowering effect when treated with timolol 0.008% or 0.025%, 42 or 0.0625%, 0.125%, or 0.25%.…”
Section: Resultsmentioning
confidence: 97%
“…All trials were randomized except one, 33 and 14 were double-masked. 34 47 Eight studies included parallel groups, 34 , 37 , 41 , 43 , 44 , 46 48 six involved dose escalation, 33 , 35 , 38 , 42 , 45 , 49 and three had one or two crossover(s). 36 , 39 , 40 Five studies enrolled healthy volunteers, 34 , 38 , 42 , 43 , 49 whereas the other 12 enrolled patients with OAG or OHT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations